Efficacy and Safety Assessment of Emulgel Containing SnakeheadFish (Ophiocephalus striatus) Dry Extract for Burn Wound Treatment in Rabbit Model - Tungadi, Robert; Njotowidjojo, Dyah Muliawati; Ruswandi, Edy; Akhyar, Akhyar; Magfirah, Rima (Journal of Experimental and Clinical Pharmacy (JECP), 2025)
Burn injuries are a significant health concern requiring effective treatment to accelerate healing and reduce complications. Conventional topical therapies often have limitations, prompting the development of alternative treatments. Snakehead fish extract, rich in bioactive compounds, has been traditionally used for wound healing. This study aimed to evaluate the efficacy and safety of an emulgel containing snakehead fish dry extract at different concentrations for burn wound treatment in rabbits. Three emulgels were formulated with extract concentrations of 0.25%, 0.5%, and 1%, then characterized for physicochemical properties, including pH, viscosity, spreadability, and adhesion. Protein content was determined using the Bradford method. An in vivo study was performed on rabbits with second-degree burn wounds, divided into five groups: negative control (emulgel base), positive control (Burnazine cream), and treatment groups receiving 0.25%, 0.5%, and 1% extract emulgel. Wound healing was assessed by measuring wound contraction for 16 days. Organoleptic tests showed no changes in color, odor, or homogeneity during four weeks of storage. The emulgel formulations showed stable physicochemical properties, with pH 6.0–6.5, viscosity 8000–10000 cPs, spreadability 6.8–6.9 cm, and adhesion time over 4 seconds, suitable for skin application. Protein content increased proportionally with extract concentration. The in vivo study showed that 1% extract emulgel significantly accelerated wound healing, with greater wound contraction compared to both controls (p < 0.05). No irritation, erythema, or edema were observed, indicating safety. The 1% snakehead fish dry extract emulgel achieved the most effective burn wound healing in rabbits. The formulation is stable, safe, and has strong potential as a natural alternative for burn treatment.